2005
DOI: 10.1007/s00438-005-0018-3
|View full text |Cite
|
Sign up to set email alerts
|

Lysine is catabolized to 2-aminoadipic acid in Penicillium chrysogenum by an omega-aminotransferase and to saccharopine by a lysine 2-ketoglutarate reductase. Characterization of the omega-aminotransferase

Abstract: The biosynthesis and catabolism of lysine in Penicillium chrysogenum is of great interest because these pathways provide 2-aminoadipic acid, a precursor of the tripeptide delta-L-2-aminoadipyl-L-cysteinyl-D-valine that is an intermediate in penicillin biosynthesis. In vivo conversion of labelled L-lysine into two different intermediates was demonstrated by HPLC analysis of the intracellular amino acid pool. L-lysine is catabolized to 2-aminoadipic acid by an omega-aminotransferase and to saccharopine by a lysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…These two enzymes are ω-aminotransferases acting on ω-aldehydes. Biochemical studies using purified enzymes of P. chrysogenum showed that those enzymes are essential for the conversion of α-aminoadipic semialdehyde into lysine and vice versa [31] (see Discussion).…”
Section: Metabolism and Energymentioning
confidence: 97%
“…These two enzymes are ω-aminotransferases acting on ω-aldehydes. Biochemical studies using purified enzymes of P. chrysogenum showed that those enzymes are essential for the conversion of α-aminoadipic semialdehyde into lysine and vice versa [31] (see Discussion).…”
Section: Metabolism and Energymentioning
confidence: 97%
“…Instead, like the HisC-derived MbnNs, these enzymes are repurposed class III ω-aminotransferases, 36 which perform transamination reactions on a wide range of substrates, including ornithine, lysine, 4-aminobutyrate, adenosylmethionine-8-amino-7-oxaononanoate, alanine, and aspartate. The top non-Mbn-related BLAST results for this group IV aminotransferase are encoded within proteobacterial operons related to amino acid catabolism, including genes for ABC amine and peptide importers and additional enzymes supporting a role in the metabolism or catabolism of aminecontaining amino acids (lysine 37 and arginine) or related compounds (GABA, 38 ornithine, 39 and biotin 40 ). The reactions catalyzed by the group IV aminotransferases are likely to be quite distinct from the reactions performed by their close homologues, just as observed with the group I MbnN and the HisC-like aminotransferases.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Often the aminotransferases of the AT-II group are also referred to as ω-transaminases (ω-ATs; [17,18,[21][22][23]). Indeed the physiological reactions of these enzymes almost invariably involve a terminal amino group or at least (e.g., in the cases of ABS or FUMAT) an amino group not located in α-position with respect to a carboxylate (Table 1); compounds containing such groups can be broadly described as ω-amines [13] 1 .…”
Section: Nomenclature Issuesmentioning
confidence: 99%